Pengaruh Disiplin Belajar Siswa Terhadap Hasil Belajar Kelas VI B MIN 3 Mojokerto - Sulistyo Wati (MODELING: Jurnal Program Studi PGMI, 2019)
Discipline is a state of behavior or behavior of a person in accordance with the rules or order so as to create order and order. This discipline helps students to fulfill their tasks and responsibilities to achieve goals. What is the discipline of MIN 3 Mojokerto students, and how is it related to student achievement? In this study, the questionnaire and documentation method were used. This research was conducted in MIN 3 Mojokerto by getting the following results: 1) Discipline of VIB students in MIN 3 Mojokerto, Mo.Mokokerto District showed a value of 62.8%. If interpreted these values ​​were in the medium category. MIN 3 Mojokerto, shows a value of 68.5%. If interpreted the medium category. 4) There is a significant influence between discipline and student learning independence on learning achievement in MIN 3 MojokertoKab.Mojokerto The coefficient value if interpreted on the interpretation coefficient correlation value can be categorized quite strong.